Hardness evaluation of dental composites fabricated from the uniform size and well-distributed zirconia-alumina-silica fillers with sol-gel technique - Hakim, Muhammad Lukman Nur; Faza, Yanwar; Hasratiningsih, Zulia; Djustiana, Nina; Sunendar, Bambang (Faculty of Dentistry Universitas Padjadjaran, 2018)
Introduction: Several factor limits of services of dental composite have triggered further improvement. ZrO2-Al2O3-SiO2 system as filler of dental composite had been developed with sol-gel technique. Ultrasonic homogeniser were reported to change the particle size ditribution or shape. Unifom size and distribution of particle is believed to help define the behavior of hardness properties. Methods: The study was an laboratory experimental design. Filler ZrO2-Al2O3-SiO2 system were developed via sol-gel methods. Post calcination process, filler were immerse in ethanol and applied with ultrasonic homogeniser, with various amplitude i.e 50 rpm, 60 rpm and 80 rpm then named sample A, B, and C. XRD, SEM anda PSA were used to characterize of filler system. Subsequent filler were used to fabricate dental composite then evaluate the hardness value using micro-hardness tester. One–way ANOVA was used to analysis the statistical result of hardness value. Results: XRD pattern of three sample were similar in which tetragonal zirconia was prominent (57-61 %) followed by monoclinic zirconia (24-25%) and amorphous (15-17 %). While, SEM and PSA characterization showed amplitude 50 rpm (sample A) produce more uniform size and well-distributed particle filler than the others. In contrary, sample B and C showed higher peak in PSA results. It means there was dominating of filler with particular size. However, the hardness value did not show significant differences between those filler (p>0,05). Conclusion: Dental composite that contain of different uniformity and distribution of filler ZrO2-Al2O3-SiO2 system has no significantly differences of hardness value.